Strengthening English Writing Ability of Students of SMP IT Cendekia Pematangsiantar Class VII Through Pro Writing Aids as Creative and Interactive Media - Tobing, Viola Sasti Bizora L.; Sinaga, Venyta; Irwansyah, Syalaisha Syafira; Herman, Herman (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
This community service activity was conducted to improve the English writing skills of Grade VII students at SMP IT Cendekia Pematangsiantar, particularly in sentence structure and vocabulary. The main objective was to enhance students’ writing ability through the use of ProWritingAid as a creative and interactive technology-based tool. The methods used included socialization, a short training session, and hands-on practice during a one-day activity involving 15 student participants. The activity was carried out actively and interactively, with direct guidance as students explored key features of the application. ProWritingAid proved useful through its grammar correction, sentence structure analysis, and writing style support. Some challenges were encountered, such as limited internet quota and restricted access to premium features. However, students showed improvement in constructing more coherent and grammatically correct English paragraphs. They also became more confident and motivated to write. This program demonstrated that the use of interactive digital media can effectively support the development of writing skills among junior high school students.